A dual circularly polarized slot‐fed horn array antenna with linear polarization‐tracking feature. Issue 9 (5th August 2018) - Vincenti Gatti, Roberto; Rossi, Riccardo
Abstract: An original architecture to generate two orthogonal circular polarizations with slotted waveguide arrays is presented in this communication. The proposed solution consists of two interleaved slotted ridge waveguide arrays sharing the same aperture and feeding a common polarizing layer represented by a dual circular polarization horn array. The radiating element realizing the linear‐to‐circular polarization conversion is made of a slot‐fed compact septum polarizer flaring into a pyramidal horn. The horn‐loaded slot model is extracted, thus allowing the synthesis of large arrays. A dual circular polarization slot‐fed horn array antenna is designed for Ku‐band operation. The two polarizations, when combined with proper phase relation, enable the tracking of two orthogonal linear polarizations. The antenna exhibits remarkable performance for both circular and linear polarization operating modes.